SEBARAN LUTUNG Trachypithecus cristatus (Raffles, 1821) DI PULAU PAHAWANG, INDONESIA - Putri Wahyuni; Indra Gumay Febryano; Dian Iswandaru; Bainah Sari Dewi (Forestry Study Program University Of Mataram, 2020)
Human and wildlife conflicts have a negative impact, especially langurs whose habitat in a small island. The study objective was to identify presence and the distribution of langurs in a small island. Data were collected using observation methods, then analyzed using descriptive analysis. The results show that there were 23 langur groups that distributed in 23 locations, with the number of smallest groups consisting of 6 individuals and the number of largest groups consisting of 12 individuals. Langur was found in the morning at 05.38 WIB-10.57 WIB and in the afternoon at 17.08 WIB-18.10 WIB. Most of these animals are found in agroforestry areas and a small part in mangrove forests. The highest activity intensity is found in the morning with the form of eating, locomotion (moving), grooming and resting activities. The existence of langurs in a small island is a good thing and must be preserved because langurs belong to protected animals. One way to conserve these animals is to create alternative conservation-based langur tourism.